(untitled) (Vietnam Journal of Community Medicine, 2024)
Background: Severe osteoporosis patients are hospitalized in many departments, have many complications, need to detect complications early, have timely treatment and treatment measures, so a unified process and coordination between many departments is needed. Objectives: Evaluate the results of the model of coordinated inpatient treatment of severe osteoporosis; Analyze the suitability and ability to maintain the model of coordinated treatment of severe osteoporosis at Thong Nhat Hospital in 2024 Subjects and methods: Study of intervention in the treatment process of severe osteoporosis patients in 3 clinical departments for 3 months. Analyze and process data using SPSS 20.0 software. Results: The length of hospital stay before and after intervention 7-14 days increased (40.5%, 64.4%), over 14 days decreased (40.5% and 24.4%). The rates of performing the examination activities of "skin color of pressure area", "pain in the injured area", "mobility" before and after the intervention were (16.7%, 51.1%, p=0.001; 38.1%, 71.1%, p=0.002; 76.2%, 100%, p=0.001), respectively. The indications for infusion of anti-resorptive drugs, thrombosis prevention, and increased pressure stockings were statistically significant after the intervention (52.4%, 77.8%, p=0.013; 40.5%, 77.8%, p<0.001; 2.4%, 31.1%, p<0.001). Specialist consultation for anti-bone resorption drug infusion (47.6%, 82.2%, p=0.001), physical therapy (16.7%, 62.2%, p<0.001). Conclusion: The initial implementation of the model of combined treatment for severe inpatient osteoporosis recorded positive results, consistent with the actual situation and the ability to continue to maintain the model in clinical departments.